2020
DOI: 10.7554/elife.59225
|View full text |Cite
|
Sign up to set email alerts
|

Ebola and Marburg virus matrix layers are locally ordered assemblies of VP40 dimers

Abstract: Filoviruses such as Ebola and Marburg virus bud from the host membrane as enveloped virions. This process is achieved by the matrix protein VP40. When expressed alone, VP40 induces budding of filamentous virus-like particles, suggesting that localization to the plasma membrane, oligomerization into a matrix layer, and generation of membrane curvature are intrinsic properties of VP40. There has been no direct information on the structure of VP40 matrix layers within viruses or virus-like particles. We present s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(93 citation statements)
references
References 48 publications
(91 reference statements)
10
77
0
Order By: Relevance
“…VP40 connects the viral nucleocapsid to the inside of the cell membrane and promotes the egress event to achieve the whole viral life cycle, which depend on its oligomerisation ability [ 13 ]. When the C-terminal domain (CTD) of VP40 attaches to cell membranes [ 14 ], it then forms polymers through self-interactions of N-terminal domain (NTD), which contributes to the release of EBOV particles [ 15 ]. VP40 can form linear hexamers and octamer rings [ 16 ]: the hexameric VP40 plays a great role in lipid raft and viral particle formation [ 17 , 18 ]; the octameric VP40 is essential for binding and viral life cycle [ 8 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…VP40 connects the viral nucleocapsid to the inside of the cell membrane and promotes the egress event to achieve the whole viral life cycle, which depend on its oligomerisation ability [ 13 ]. When the C-terminal domain (CTD) of VP40 attaches to cell membranes [ 14 ], it then forms polymers through self-interactions of N-terminal domain (NTD), which contributes to the release of EBOV particles [ 15 ]. VP40 can form linear hexamers and octamer rings [ 16 ]: the hexameric VP40 plays a great role in lipid raft and viral particle formation [ 17 , 18 ]; the octameric VP40 is essential for binding and viral life cycle [ 8 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobic interaction at the hexamer-hexamer interface may provide an agile interface, giving flexibility to the filaments. (E) Zoom into hexamer-hexamer interface in the mVP40 filament formed through CTD-CTD linear oligomerization as proposed by Wan et al (Wan et al , 2020). (CTD from each monomer is in showed in different colors)…”
Section: Resultsmentioning
confidence: 94%
“…It is possible that NTD-NTD interactions are required to increase membrane bending, elongation of tubule and/or for host cell factor recruitment at assembly sites. Furthermore, using the recent model proposed in CTD-CTD linear oligomerization ((Wan et al , 2020), Fig. S6), we simulated the CTD-CTD complex that indicated this interface may involve Met 191 , Asn 222 , Tyr 195 and Leu 226 as we report here (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…VP40 is sufficient to drive virion budding and is responsible for the characteristic filamentous shape [23]. Recent cryo-ET studies revealed the organization of VP40 proteins in budded particles into an apparent helical scaffold lining the inner viral membrane leaflet [21]. Besides VP40 as a major driver of EBOV budding, actin has been shown to be indispensable, since the disruption of the actin cytoskeleton abrogates particle formation [24].…”
Section: Introductionmentioning
confidence: 99%